Penyuluhan Kesehatan Gigi Dengan Metode Permainan Ular Tangga Pada Anak - Sandriani Sandriani; Hiban Hilmansyah; Dede Sanusi (Yayasan Inspirasi El Burhani, 2023)
Introduction: A susceptible population for dental and oral health is schoolchildren. Children's oral hygiene habits can be altered via the promotion of dental health. because kids at this age are still growing and developing, and they require their parents' care and support. Objective: The goal of this volunteer work is to promote students' knowledge of dental and oral health using the Snakes and Ladders Game Method and Caries Prevention by Smearing Flour to Students. Method: Children are also practised brushing their teeth correctly and properly while being watched. The capacity of the kid to independently brush their teeth in the proper manner and greater understanding of the need of maintaining healthy teeth and mouth from an early age in order to avoid tooth decay are signs that this activity was carried out successfully. Next, sprinkle flour on children's primary school teeth to prevent dental cavities, especially on permanent teeth. Result: Snakes and ladders games and direct demonstrations using dental models were used in dentistry and oral health education to educate pupils how to wash their teeth properly. This demonstrates the significance of teaching elementary school students about dental health so that they may comprehend the method and how to appropriately wash their teeth. The child's permanent teeth are then treated with topical fluoride after the teeth and mouth are examined. Conclusion: Activities that extend outside the classroom can help youngsters learn more about the value of maintaining healthy teeth, as well as how to prevent dental and oral diseases.”